EMPATHY DAN DESIGN THINKING DALAM INOVASI MANAJEMEN PENDIDIKAN ISLAM DI ERA DISRUPTIF - Afina Mauliya; Suci Wulandari (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2021)
Abstract the phenomenon of the current disruptive era makes technology develop fast paced. The rapid progress must be matched with the ability of human resources as the executor of the organization. This study aimed to find out the management innovation in Islamic education institution that nowadays becomes a serious concern to face the global competition. The abilities of empathy and design thinking are the skills that need to be had by headmasters in facing the disruptive era. Innovation in Islamic education management is essential to do considering that the success of education goals is seen from how to manage an organization. This study is the result of literary research sourced from indexed scientific journals, books, and news on the internet. The procedures used included three phases, namely organize, synthesize, and identify. The result of content analysis showed the concept of design thinking as the process to obtain problem solving which is relevant to the education field namely the formulation of new policy and analysis towards a problem by collecting analyses so that it is helpful to obtain right and effective decision making. Abstrak Fenomena era disruptif saat ini menjadikan teknologi berkembang serba cepat. pesatnya kemajuan harus diimbangi dengan kemampuan SDM sebagai pelaksana organisasi. Penelitian ini bertujuan untuk menggali inovasi manajemen di lembaga pendidikan Islam yang saat ini menjadi perhatian serius untuk menghadapi persaingan global. Kemampuan empati dan design thinking adalah skill yang harus miliki oleh kepala sekolah dalam menghadapi era disruptif. Inovasi dalam manajemen pendidikan Islam penting dilakukan mengingat keberhasilan tujuan pendidikan dilihat dari cara mengelola organisasi. Penelitian ini merupakan hasil riset kepustakaan dengan referensi jurnal ilmiah terindeks, buku dan berita di internet. Prosedur yang digunakan meliputi 3 tahap, yaitu organize, synthesize dan identify. Hasil analisis isi menunjukkan konsep design thinking sebagai proses menghasilkan problem solving relevan dalam dunia pendidikan khususnya perumusan kebijakan baru dan analisis terhadap suatu permasalahan dengan mengumpulkan analisa-analisa sehingga membantu dalam upaya pengambilan keputusan yang tepat dan efektif.